GC columns as micro-air samplers for the quantitative analysis of naphthalene vapours. Issue 3 (20th December 2016) - Gura, Sigalit; Madmon, Moran; Tzanani, Nitzan; Barak, Ruth; Shacht, Israel; Dagan, Shai
Abstract : Although linked to a number of adverse health effects, studies of naphthalene are lacking in the exposure-relevant literature. Abstract : Although linked to a number of adverse health effects, studies of naphthalene are lacking in the exposure-relevant literature. This compound, a major by-product of the incomplete combustion of most organic materials (traffic vehicle exhaust, power generation, tobacco smoke, etc. ), has characteristics that are in between those of volatile and semivolatile organic compounds (VOCs and SVOCs) and has consequently often been excluded from studies of both compound classes. A new, highly quantitative, rapid and spatially well-resolved micro-sampling method was developed for the sampling of naphthalene vapours in indoor, outdoor and personal air. The method is based on GC capillary columns as air samplers, solvent extraction and GC-MS analysis. For the first time, naphthalene concentrations were quantitatively determined at the surface level (around the boundary layer) and at 1 mm height intervals above an emitting surface. Minimal sampling flow rates of 5 mL min −1 were applied to reduce any geometrical or dynamical disturbance to the environmental air flow regime to a minimum. Toluene was highly efficient, precise and easy to apply in the extraction of the target compound from the GC column sampler. Method quantification was confirmed using a unique calibrated vapour generator based on an inert GC inlet. Using this source, a 13 ng L −1 limit of quantitation (LOQ) with 90% mass recovery over a linear dynamic range of five orders of magnitude in high precision and accuracy of ±13% and 35%, respectively, were determined and validated. The applicability and flexibility of the method was demonstrated by investigating the vapour concentration profiles generated "0"–20 mm above a naphthalene-emitting surface in outdoor air. The concept introduced in this research could be easily adopted for the reliable, sensitive and quantitative monitoring of other VOCs and SVOCs in different micro-spaces for various applications.